2017
DOI: 10.1103/physrevx.7.011026
|View full text |Cite
|
Sign up to set email alerts
|

Prethermal Phases of Matter Protected by Time-Translation Symmetry

Abstract: In a periodically driven (Floquet) system, there is the possibility for new phases of matter, not present in stationary systems, protected by discrete time-translation symmetry. This includes topological phases protected in part by time-translation symmetry, as well as phases distinguished by the spontaneous breaking of this symmetry, dubbed "Floquet time crystals". We show that such phases of matter can exist in the pre-thermal regime of periodically-driven systems, which exists generically for sufficiently l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
495
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(522 citation statements)
references
References 105 publications
(160 reference statements)
23
495
4
Order By: Relevance
“…Another possibility is that the observed DTC falls into the short time regime before reaching the prethermal state, as suggested in Ref. 26 . Clearly, by tuning driving frequency and other couplings, the complex interplay between interactions and disorder may either further strengthen DTC behavior or lead to competing phases 28 .…”
Section: Introductionmentioning
confidence: 81%
“…Another possibility is that the observed DTC falls into the short time regime before reaching the prethermal state, as suggested in Ref. 26 . Clearly, by tuning driving frequency and other couplings, the complex interplay between interactions and disorder may either further strengthen DTC behavior or lead to competing phases 28 .…”
Section: Introductionmentioning
confidence: 81%
“…[10][11][12][13]. References [14][15][16][17] even showed that a driven disordered system in one dimension (1D) could spontaneously break the discrete time translation symmetry, forming the long-sought-after time crystal, while Refs. [18][19][20] showed that a periodic drive can delocalize a many-body localized system.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the system is assumed to be in a localized phase [33,34,36,37] or to have long-range interactions [38][39][40]. Otherwise, the DTC order only exists in a prethermalized regime [41,42] since the system will eventually be heated to a featureless infinite-temperature state due to persistent driving [43][44][45].While remarkable progresses are being made concerning the DTC phase, most studies focus on isolated systems. Indeed, as has been experimentally observed [37,38] and theoretically investigated [46], the DTC order in an open system is usually destroyed by decoherence.…”
mentioning
confidence: 99%